Mathematical Modeling using Differential Equations, and Network Theory - Dassios, Ioannis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue collects the latest results on differential/difference equations, the mathematics of networks, and their applications to engineering and physical phenomena. It features nine high-quality papers that were published with original research results. The Special Issue brings together mathematicians with physicists, engineers, as well as other scientists.